Microvascular Anastomoses Using End-to-End versus End-to-Side Technique in Lower Extremity Free Tissue Transfer - Cho, Eugenia H.; Garcia, Ryan M.; Blau, Jared; Levinson, Howard; Erdmann, Detlev; Levin, L. Scott; Hollenbeck, Scott T. (Journal of Reconstructive Microsurgery, 2016)
Background The decision to perform an end-to-end (ETE) or end-to-side (ETS) arterial anastomosis in lower extremity free tissue transfer has not been thoroughly evaluated in a large multisurgeon setting. The authors compared the reconstructive outcomes of lower extremity free flaps with ETE and ETS arterial anastomoses.Methods The authors retrospectively reviewed their 17-year institutional experience with lower extremity free flaps to determine whether ETE or ETS arterial anastomoses were associated with foot ischemic complications and flap failure.Results From 1996 to 2013, 398 patients underwent 413 lower extremity free flaps with ETE (66%) or ETS (34%) arterial anastomoses. The incidence of postoperative foot ischemia was 2% (n = 8). The flap failure rate was 11% (n = 45). The ETS technique was preferred in patients with fewer intact vessels to the foot (32% ETS for three-vessel runoff, 36% ETS for two-vessel runoff, and 50% ETS for single-vessel runoff) and when an intact recipient vessel was selected for anastomosis (60% ETS for intact vessel vs. 25% ETS for distally occluded vessel). No differences were observed in the foot ischemia (p = 0.45) and flap failure rates (p = 0.59) for ETE versus ETS arterial anastomoses. In subset analyses, the incidence of foot ischemia did not differ for either technique in the context of impaired vascular runoff or recipient vessel selection.Conclusion No advantage was noted for ETE or ETS arterial anastomoses based on reconstructive outcomes. The choice of anastomotic technique in lower extremity free tissue transfer should be based on patient factors and the clinical circumstances encountered.
Keywords: lower extremity; microvascular anastomosis; free tissue transfer; free flap; anastomosis